Revolutionizing cancer treatment: nanotechnology-enabled photodynamic therapy and immunotherapy with advanced photosensitizers - Jia, Jiedong; Wu, Xue; Long, Gongwei; Yu, Jie; He, Wei; Zhang, Huiping; Wang, Dongwen; Ye, Zhangqun; Tian, Jun (Frontiers in Immunology, 2023)
Nanotechnology-enhanced photodynamic therapy (PDT) and immunotherapy are emerging as exciting cancer therapeutic methods with significant potential for improving patient outcomes. By combining these approaches, synergistic effects have been observed in preclinical studies, resulting in enhanced immune responses to cancer and the capacity to conquer the immunosuppressive tumor microenvironment (TME). Despite challenges such as addressing treatment limitations and developing personalized cancer treatment strategies, the integration of nanotechnology-enabled PDT and immunotherapy, along with advanced photosensitizers (PSs), represents an exciting new avenue in cancer treatment. Continued research, development, and collaboration among researchers, clinicians, and regulatory agencies are crucial for further advancements and the successful implementation of these promising therapies, ultimately benefiting cancer patients worldwide.